IMPROVING READING COMPREHENSION ABILITY USING THE CREATIVE SIMULATION METHOD STUDENTS OF CLASS V SD INPRES MACCINI SOMBALA I MAKASSAR CITY - Ulfiani Safitri; Nursamsilis Lutfin (Teaching English as a Foreign Language Overseas Journal, 2022)
This type of research is classroom action research (PTK) which is divided into two cycles of 3 meetings with 4 stages, namely planning, action, observation and reflection which are carried out repeatedly. The reading comprehension ability of class V SD Inpres Maccini Sombala 1 City is still below the Minimum Completeness Standard (KKM). This is because in class management, the presentation of material is still monotonous so students are less interested in learning to read. The teacher's dominance in the learning process so that students are less interested and passive in receiving lessons. Conditions like this will be solved through the use of creative simulation methods. Increasing the average ability score reading comprehension of students during this research was conducted, namely 65.68 in cycle I and to 86.88 in cycle II. And the learning mastery of students' reading comprehension skills also increased, namely in cycle I of 25 students only 11 people or 44% who completed it increased to 23 people or 92% in cycle II. Increased reading comprehension skills from cycle I to cycle II caused by student learning activities that are relevant to learning also experienced a quite encouraging increase, where students who Pay attention to the teacher's explanation, students who ask questions, students who answer questions from the plays read, students doing simulations in front of the class, and students asking questions increased to very high category.